2023
DOI: 10.1186/s12951-022-01753-7
|View full text |Cite
|
Sign up to set email alerts
|

Silica nanoparticles promote wheat growth by mediating hormones and sugar metabolism

Abstract: Background Silica nanoparticles (SiNPs) have been demonstrated to have beneficial effects on plant growth and development, especially under biotic and abiotic stresses. However, the mechanisms of SiNPs-mediated plant growth strengthening are still unclear, especially under field condition. In this study, we evaluated the effect of SiNPs on the growth and sugar and hormone metabolisms of wheat in the field. Results SiNPs increased tillers and elonga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 50 publications
(53 reference statements)
2
17
0
Order By: Relevance
“…reported that foliar application of 200 mg/L Si NPs significantly increased the sugar content (e.g., glucose, sucrose and fructose), enhanced photosynthesis, accelerated sugar synthesis and transport, and modulated phytohormone levels in wheat ( Triticum aestivum L.) 66 . In that work, the authors hypothesised that the mechanism was increased expression levels of genes related to soluble sugars ( SPS , SUS and α‐glucosidase), chlorophyll ( CHLH , CAO , and POR ), IAA ( TIR1 ), and ABA ( PYR/PYL , PP2C , SnRK2 , and ABF ) 66 . Similarly, foliar application of 60 mg/L SiO 2 NPs significantly increased the accumulation of AAs (e.g., glutamine, arginine and valine) and sugars (e.g., fructose and glucose) in cucumber 48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that foliar application of 200 mg/L Si NPs significantly increased the sugar content (e.g., glucose, sucrose and fructose), enhanced photosynthesis, accelerated sugar synthesis and transport, and modulated phytohormone levels in wheat ( Triticum aestivum L.) 66 . In that work, the authors hypothesised that the mechanism was increased expression levels of genes related to soluble sugars ( SPS , SUS and α‐glucosidase), chlorophyll ( CHLH , CAO , and POR ), IAA ( TIR1 ), and ABA ( PYR/PYL , PP2C , SnRK2 , and ABF ) 66 . Similarly, foliar application of 60 mg/L SiO 2 NPs significantly increased the accumulation of AAs (e.g., glutamine, arginine and valine) and sugars (e.g., fructose and glucose) in cucumber 48 .…”
Section: Resultsmentioning
confidence: 99%
“…66 In that work, the authors hypothesised that the mechanism was increased expression levels of genes related to soluble sugars (SPS, SUS and α-glucosidase), chlorophyll (CHLH, CAO, and POR), IAA (TIR1), and ABA (PYR/PYL, PP2C, SnRK2, and ABF). 66 Similarly, foliar application MODERN AGRICULTURE of 60 mg/L SiO 2 NPs significantly increased the accumulation of AAs (e.g., glutamine, arginine and valine) and sugars (e.g., fructose and glucose) in cucumber. 48 Taken together, Si-based NMs can promote the accumulation of AAs and carbohydrates in radish, thereby increasing plant yield and improving fruit nutritional quality.…”
Section: Metabolomics Of Radish Edible Tissuementioning
confidence: 99%
“…The application of silicate and SiO 2 NPs through foliar spray resulted in increased fresh weights of both shoots and roots compared to the control group exposed to salinity alone (Figure S2). Similarly, the enhancement of plant biomass has been observed in sorghum, wheat, and maize through foliar spraying of Si/SiO 2 NPs.…”
Section: Resultsmentioning
confidence: 72%
“…This is supported by literature where increases in chlorophyll content have previously been correlated with overall plant health upon silica NP treatments. 48,49 Changes in Biomass after NP Treatment. The fresh biomass was also measured for healthy and diseased plants that were treated with foliar or seed applications of MSNs and CTS-MSNs, as well as for untreated controls (Figure 5).…”
Section: ■ Introductionmentioning
confidence: 99%